Nghiên cứu các chất quang xúc tác TiO2 được biến tính bằng Fe2O3 bằng phương pháp sol-gel - Tuấn, Nguyễn Quốc; Lộc, Lưu Cẩm; Thoảng, Hồ Sĩ (Vietnam Journal of Chemistry, 2014)
Thin layers of pure TiO2 and TiO2 doped by different amounts of Fe2O3 have been prepared by sol-gel method with tetraisopropyl orthotitanate and Fe(NO3)3. Physico-chemical properties of the catalysts were studied by the methods of BET Adsorption, X-ray Diffraction (XRD), FE-SEM, as well as Raman, IR and UV-Vis spectroscopies. Photocatalytic activity of the obtained materials was investigated in the reaction of complete oxidation of p-xylene in gas phase under the radiation of UV (l = 365 nm) and Blue LED (l = 470 nm) lamps. It has been found that particle’s size of all the samples is distributed in the range of 20-30 nm. The content of rutile phase in Fe-doped TiO2 samples varied from 6.8 to 41.8% depending on the Fe content. Iron oxide doped into TiO2 enables to move the photon absorbing zone of TiO2 from UV toward visible wave lengths as well as to reduce its band gap energy from 3.2 eV to 2.67 eV. Photocatalytic activities of the TiO2 samples promoted by Fe3+ have been found to be higher than those of pure TiO2.